ISMAIL AL-FARUQI DAN FAHAM ISLAMISASI ILMU - Ahmad Nabil Amir (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2021)
The paper analyzed Ismail Raji al-Faruqi’s (1921-1986) ideas on Islamization of knowledge and his critical contribution in articulating modern Islamic worldview and expounding its progressive and inclusive outlook. It discusses his deeply significant framework and methodology in articulating the ideas of Islamization of knowledge and propounding major doctrine of tawhid in the light of his works such as Islamization of Knowledge: General Principles and Work Plan, Al-Tawhid: Its Implications for Thought and Life dan etc. The study is based on library research using qualitative approaches by documenting sources derived from some major works of al-Faruqi and other relevant materials. The data was analyzed using descriptive, analytical, and comparative method. The study concluded that al-Faruqi has bring forth universal Islamic worldview that propounded transcendental religious and philosophical outlook based on his rational and universal premises. His philosophical ideal was founded on critical methodology of tawhid that was instrumental in projecting his Islamization of knowledge movement and in propounding its scientific and rational outlook in order to revived the spirit of reform and reconstructing ijtihad and reclaiming the universal and creative ummatic world order.